A stranger in a foreign land: Identity transition in blogs about transnational relocation. (August 2020) - Walz, Linda; Fitzgerald, Richard
Highlights: Expatriate blogging is a discursive practice of everyday sense-making over time. Bloggers engage with living abroad both as a personal and a categorial experience. What is taken for granted changes as bloggers experience and relate life abroad. Identity in transnational relocation is inherently dynamic and transitional. Membership categorisation analysis provides a way of exploring identity as fluid. Abstract: Moving to a different country has become an established part of a globalised economy, and such transnational movement has engendered a rich genre of writing describing this phenomenon. The internet has provided a new means of making sense of this experience through 'expatriate' blogging. In these blogs the experience of dislocation and relocation, of moving from the taken for granted to uncertainty, is described from the position of being an 'expat', a 'non-local', or a 'stranger' (Schuetz, 1944 ). Relocation provides a point of reflection as once familiar routines are questioned and initially unfamiliar ones are becoming more established. Whilst this transition is often experienced as a personal one, in the genre of expatriate blogging individuals relate their experience through personal and public self-reflection. Afforded by the chronological nature of these blogs, individuals draw on time as a resource to document their transition, highlighting an evolving identity. In this paper we use Membership Categorisation Analysis to examine expatriate blogging as a discursive practice, and we explore analytically how to approach social identity as fluid and evolving where transnational relocation is framed as categorial transition.